Internationalization of Education Policy : A New Constellation of Statehood in Education? - Martens, Kerstin; Knodel, Philipp; Windzio, Michael; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book investigates and discusses the phenomenon of internationalization of education policy and its consequences for national policymaking processes. By comparing educational outcomes and actors' reactions in different countries, it provides detailed insights into a highly contested policy field.
Keywords: Science; Science, general